Children's Communication BehaviorDue To Gadget Dependence (Case Study in the Tanjung Raya Permai Housing Complex, RT 07, Pematang Wangi Village, Bandar Lampung) - Naufal Hafizhoh; Wawan Hernawan; Muhammad Denu Poyo (Cita konsultindo, 2026)
This study aims to explore the communication behavior of children who are dependent on gadgets, specifically within the community of Tanjung Raya Permai Housing Complex in Bandar Lampung. The background of this research stems from the increasing use of digital devices among children, which is believed to affect their social interactions and interpersonal communication patterns. Using a qualitative approach with a case study method, the data will be collected through observations, in-depth interviews with children, parents, and as well as relevant documentation. The focus is to understand how gadget usage may influence the way children express themselves, interact with others, and build relationships in both family and social settings. The study also seeks to provide input for developing healthier communication patterns between children and their environment in the digital era.